Developing UNO English Card Game and Its’ Impact to the EFL Students’ Descriptive Writing Performance - Afif Ikhwanul Muslimin; Fitrana Harintama (ELITE JOURNAL, 2022)
This study is aimed to develop a card game to scaffold the obstacles of EFL students to compose descriptive text. The research and development design were applied to achieve the UNO English card game through modifying the conventional UNO cards with the descriptive text English material. The participants were the eight students joining the Writing I course in Banking Department in a public Islamic university in Indonesia. The results showed that the application of the UNO English card through game-based learning model could minimize the EFL students’ descriptive writing errors as well as increasing their interest joining the EFL class. Therefore, comparing the students works in both pretest and posttest, it was known that the EFL students’ descriptive writing scores had increased due to the treatment of UNO English card application. This study unveils demand for EFL teachers’ creativity to elevate the EFL class outcome through more interesting activity and material development. Keywords: EFL, descriptive writing, game-based learning, UNO English card